The role of higher education in generating 'public' and 'common' goods: A comparison of Sinic and Anglo-American political cultures - Marginson, S; Yang, L (Centre for Global Higher Education, University of Oxford, 2020)
CGHE Working Paper 52 by Simon Marginson and Lili Yang compares Sinic and Anglo-American approaches to the role of higher education in generating public and common goods. It parallels the two higher education systems in the light of their political and educational cultures and their approaches to collectivism and individualism.